Diatoms-endoparasite association in fish from the marine pacific coast of Colombia (Buenaventura). - Vanessa Potosi-Pai; Carlos E Agudelo Morales; Javier Antonio Benavides-Montaño (PLoS ONE)
The association of parasites and diatoms has been previously reported as an important mechanism to control bacteria and parasites to avoid resistance to chemical usage. The aim of this study was to investigate the association between diatoms genus and parasites within the gastrointestinal compartments (GICs) of commercial fish in fisheries of the marine Pacific coast of Colombia (Buenaventura). A total of 104 GICs from marine fish were sampled. The GICs analysis revealed 14 diatom genera (N = 14). The most prevalent were Coscinodiscus spp., which was present in 58/104 samples, 55.8% [95% CI = 37.5-62.1%]; Cyclotella spp., 28/104, 26.9% [95% CI = 0-25%]; Paralia spp., 26/104, 25% [95% CI = 12.5-44.8%]; Gyrosigma spp., 11/104, 10.6% [95% CI = 0-33.3%]; Navicula spp., 11/104, 10.6%, [95% CI = 0-20.7%]. The GICs analysis revealed a diversity of genera parasites. The most prevalent were Ameboid cysts, 25/104, 24% [95% CI = 12.5-48.3%]; Eimeria spp., 11/104, 10.6% [95% CI = 10.3-15.7%]; Anisakis spp., 29/104, 27.1% [95% CI = 27.1 (SD±12.9%)]. This is the first report concerning diatoms and parasites association in fish from the Pacific Coast of Colombia and highlights the relevance of Coscinodiscus spp. and Gyrosigma spp. as important diatoms and potential candidates for studying pharmaceutical action in aquaculture. Further studies about diatoms-parasites association in aquaculture are required.